Eskalasi Sentimen Positif Terhadap Loyalitas Konsumen Melalui Optimalisasi Strategi Pemasaran - Zahro, Nikmatuz; Wahyuningsih, Rita (Universitas Duta Bangsa Surakarta, 2024)
Business development is an indicator of economic progress so that in the process it experiences various kinds of changes which pressure companies to continue to adapt to business developments. The aim of this research is to examine in general the field factors that can influence the increase in positive sentiment towards consumer loyalty through various business strategies. The research methodology is direct observation and is included in the field research category, which is direct observation of the object being studied. This study contains the general population which is interpreted into three objects, namely Toko Emas A, Toko Emas B, and Toko Emas C. The research results show that indirectly Toko Emas A can be said to be superior because of its strategic location, excellent service, and good supporting facilities. can make it easier for consumers, as well as good product displays and layout so as to provide comfort to consumers. Toko Emas A implements marketing strategies well and thoroughly, which will get a positive response and can increase consumer interest in buying the products offered. The compatibility between theoretical knowledge and field implementation so that it can be used as a basis for developing marketing strategies by companies.